Formulasi Strategi Penghimpunan Zakat oleh Badan Amil Zakat Nasional (BAZNAS) - Ita Aulia Coryna; Hendri Tanjung (Department of Islamic Economics, IPB University, 2015)
As the most populous Muslim nation in the world Indonesia has the largest zakat potential, yet its’ zakat collection on national level only reached 1% of the whole potential. This matter has become the greatest challenge for all zakat institutions in Indonesia, especially the National Amil Institution (BAZNAS). Recently the government made a new regulation; Inpres No.3/2014, that could help the institution to minimize the discrepancy between zakat potential and zakat realization. The main objective of the paper is to formulate a strategy for BAZNAS to optimized its zakat fund’s collection in regards to the new regulation, where BAZNAS is specifically asked to coordinate and to collect zakat from all of government’s institutions. Data is collected using a survey questionnaire on both internal and external representatives of BAZNAS, and is analyzed using SWOT matrix.